Policies for school climate in an era of accountability - Ascorra, Paula; Carrasco Aguilar, Claudia; López, Verónica; Morales, Macarena (Education Policy Analysis Archives, 2019)
Over the past 15 years, Chile has implemented three different educational laws and policies to enhance, promote and develop school climate (SC). However, different logics of understanding and intervening in SC underlie these legal bodies. In order to account for the contradictions and critical nodes of instruments that conform Chile´s SC public policy, we performed a documentary analysis of laws and other key documents. Using content analyses, we identified four critical nodes: contradiction between declaration and measurement of quality of education; explicit arrangements for institutional sanctions, which contrasts with ambiguity about institutional supports; contradictory understandings about SC; and differential treatment for public and private schools. We discuss the possibilities of promoting a democratic SC in a policy environment that is highly oriented by accountability.